A new method to measure the rationalities of transit route layouts. Issue 4 (December 2020) - Akgol, Kadir; Gunay, Banihan; Eldemir, Fahrettin; Samasti, Mesut
Highlights: This study offer a new method to measure the rationalities of transit routes. Measurements are performed for all transit journey combinations. The method is capable of ranking bus services with respect to route geometry. Abstract: Public transport routes (especially urban bus routes) may become tedious and lengthy due to undesired deviations from the target destination directions. This makes public transport less attractive compared to other modes. Optimization of bus route layouts (under the name of rationalisation) ought to concentrate on, primarily, the quantification of the shape (geometric) features of these routes. The present paper has therefore developed a numerical method for measuring the benefits of improving these route layouts. Using the method developed, over one million public transport journeys on 1242 bus lines in Istanbul Metropolitan City have been analysed. For each bus route, rationality values have been calculated and geocoded on GIS to produce a "digital rationality map" of the whole city. In addition, to be able to see the rationality changes by region, the map has been broken into municipal districts. As a result, particularly irrational bus routes were easily identified. The findings have already been taken on board by the National Research Council for immediate consideration of potential improvements and further research directions.